Quantification of sediment transport through direct measurements and the use of empirical models in an experimental catchment in the Andes Mountains, Southern Chile. - Iroumé, Andrés; Uyttendaele, Paula (Revista Técnica da Faculdade de Engenharia da de Zulia)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–> The quantification of sediment transport is very important in engineering studies and in the design of dams and bridges, but at the same time is one of the most difficult tasks to undertake. Sediment transport monitoring is expensive especially in small mountain catchments, and requires long records to account for its very high variability. This study summarizes the quantification of sediment transport and the validation of different sediment transport models in a 5.93 km2 catchment located in the Andes Mountains in Southern Chile. From October 1997 to May 2005, total sediment transport was 7.1 * 103 tons (mean sediment transport rate of 171 ton/year/km2) in which suspended sediment participated with the 55.7%. Suspended sediment transport varied between 17 and 1084 ton/year while bedload ranged from 14 to 677 ton/year. For a range of discharges lower than 2.14 m3/s the different transport models overestimated sediment transport, the exception being those proposed by Van Rijn and Bathurst. The Bathurst model is proposed for sediment transport estimation in ungauged mountain catchments near the study area.